AN AI-DRIVEN SPEECH ANALYSIS FOR ENHANCING COMMUNICATION AND PUBLIC SPEAKING IN GLOBAL SOFTWARE DEVELOPMENT - Farwah Aizaz; Fatima Nazir Rani; Laiba Ehsan; Shamas Ur Rehman; Malik Talha Tariq (Spectrum of Engineering Sciences, 2025)
This paper takes a close look at how teams working across different countries often struggle with communication and how an AI tool called Orator Path might help make those conversations clearer and more effective. Working in software teams that are spread out across the globe comes with its fair share of communication problems. People speak differently, accents vary, and sometimes the way someone says something doesn’t come across as they meant it. This can cause confusion or slow things down. While teams usually rely on calls, chat apps, and emails, those don’t really help someone improve the way they talk or present. That’s what this paper is about: exploring how a tool called Orator Path uses AI to give people direct feedback on how they speak. It looks at things like clarity, how fast they’re talking, their tone, and even facial detection. The idea is to help people become more confident when talking, especially in remote teams. We also go into the tech side a bit, like how machine learning, NLP, and vision tools are used, but the main focus is on how this can actually help in real team settings. There are, of course, challenges with using AI this way, and we talk about those too. In short, it’s about using smart tools to help people talk better, not just more.